PENGARUH BAURAN PEMASARAN E-COMMERCE TERHADAP INTENSI PEMBELIAN MODUL ASYNCHRONOUS E-LEARNING: PERAN DARI PENGETAHUAN KONSUMEN - Deny, Deny (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
Research in the E-Learning business is still limited and more research is needed on the purchase of online courses, especially the Asynchronous modules that are available at several providers of paid E-Learning platforms. The sample of this study was 100 visitors to the schoolpintar.com and Kelaskita.com sites using SEM analysis techniques. The results of this e-learning study show that the intention to purchase asynchronous e-learning modules is not significantly affected by product attractiveness, price perception and consumer knowledge, but is significantly influenced by marketing effectiveness. The results of this study are useful for entrepreneurs and prospective online business business entrepreneurs to be able to increase sales of online courses in Indonesia by focusing on marketing efforts specifically to change consumer preferences and beliefs. Keywords: e-learning, asynchronous online learning, purchase intention, consumer knowledge